Determinants of ARYA Adoption for Livelihood Security in Nalgonda district of Telangana - Deekshith, Bachali; Doharey, R K; Meena, N R; Sonu, Kumar; Shankar Mishra , Jay (Indian Journal of Extension Education, 2025)
The study was conducted during 2023-25 to identify the determinants influencing the adoption of the ARYA programme in Nalgonda district. Employing a multistage random sampling technique, data were collected from 160 rural youth across four agriculturally prominent blocks using structured interview. The analysis revealed that the integrated farming system emerged as the most widely adopted component of the ARYA programme, followed by animal husbandry and horticultural activities. 70.63 per cent of respondents exhibited medium adoption levels, indicating partial engagement with programme components. Correlation analysis identified attitude (r = 0.753**) and knowledge (r = 0.738**) as the most significant predictors of adoption, while education, landholding, annual income, and extension contact also showed strong positive associations. The study highlighted critical gaps in the adoption of marketing and post harvest practices, suggesting the need for strengthening forward linkages, value addition infrastructure, and market accessibility. The findings emphasised the importance of targeted awareness campaigns, skill enhancement initiatives, and institutional support to promote entrepreneurship among rural youth. Strengthening extension services and refining programme implementation strategies can enhance adoption levels, ensuring livelihood security and sustainable development in rural communities.
Keywords: ARYA; Livelihood security; Adoption; Integrated farming system; Rural youth